Exploring lifelong learning outcomes among adult learners via goal orientation and information literacy self-efficacy - Ong Choon Hee; Lim Lee Ping; Adriana Mohd Rizal; Tan Owee Kowang; Goh Chin Fei (Institute of Advanced Engineering and Science, 2019)
This study intends to explore the relationship between goal orientation, information literacy self-efficacy and lifelong learning outcomes of the adult learners. This study focuses on adult learners as they are actively participating in the development of the country socio-economy and recognized as the potential contributors towards the generation of knowledge-based economy. The findings of this study revealed that there was a significant relationship between mastery goal orientation and lifelong learning. However, information literacy self-efficacy was found to be a predictor instead of a moderator in the model. It is suggested that suitable and appropriate learning methods such as problem-based learning, case scenario presentations, portfolios and clinical debates can be designed specifically to facilitate adult learners’ mastery goal learning motivation in promoting lifelong learning. In addition, training and retraining to equip adult learners with new information literacy skills so as to keep up their self-efficacy level will definitely enhance lifelong learning. This study provides a database on the impact of goal orientation and information literacy self-efficacy towards lifelong learning in implementing policy formation, educational structure redesign and human capital development. As such, suitable and appropriate learning methods such as problem-based learning, case scenario presentations, portfolios and clinical debates can be designed specifically to facilitate student learning motivation in the classroom.